Menggali Makna Kewarganegaraan Dalam Era Globalisasi - Rahma Azizah; Fadhila Rahmi; Gezla Dwi Afira; Rezika Ali; Audry Rialnita Butar-Butar , Helfira Citra (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
This research aims to understand the important role of citizenship in facing the era of globalization so that we do not make mistakes in making decisions. In this era of globalization, the role of digital is very influential so that we as citizens must be clever in sorting out what is good and what is not. Globalization is a  the process of a global social order that does not recognize territorial boundaries. Globalization is essentially a process of ideas that are emerged, then offered for other nations to follow, which ultimately reaches a point of mutual agreement and becomes a common guideline for nations throughout the world (Edison A  .Jamli, 2005). Technological advances in the 4.0 era have created anxiety for citizenship, which has become a challenge in the life of the nation and state today.